The dinkey donkey - Smith, Craig, 1972-; Cowley, Katz, 1973- (New York : Scholastic Inc., 2019)
Originally written as a children's song, Wonky Donkey has a daughter, cute and small, and prone to mischief.
K-3
English
Keywords: Children's songs, English -- United States -- Texts; Donkeys -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Stories in rhyme; Donkeys -- Songs and music -- Text; Horse family (Mammals) -- Songs and music -- Text; Mothers and daughters -- Songs and music -- Text; Songs; Picture books; Stories in rhyme